Generative and Transformational Techniques in Software Engineering: International Summer School, GTTSE 2005, Braga, Portugal, July 4-8, 2005 : Revised Papers - Lämmel, Ralf; Saraiva, João; Visser, Joost (Lecture notes in computer science, 2006)
This tutorial book presents an augmented selection of the material presented at the International Summer School on Generative and Transformational Techniques in Software Engineering, GTTSE 2005, held in Braga, Portugal, in July 2005. The 7 tutorial lectures presented together with 8 technology presentations and 6 contributions to the participants workshop were carefully selected during multiple rounds of reviewing and improvement. The tutorials given by renowned representatives of complementary approaches and problem domains combine foundations, methods, examples, and tool support. They deal with the following subjects: feature oriented programming and the AHEAD tool suite; model driven engineering; program transformation with reflection and aspect-oriented programming; the transformational approach to database engineering; program optimizations and transformations in calculation form; mappings in data processing; and the use of graph transformations for model refactoring.